Caveolin-1, a driver of invasive phenotype in in-vitro 3D-spheroid assays comprised of high grade GBM cells association with an AKT-inhibited phenotype. (31st January 2018) - Moriconi, Chiara; Palmieri, Valentina; tornillo, giusy; Fillmore, Helen; Pilkington, Geoffrey J; Gumbleton, Mark
Abstract: INTRODUCTION: Glioblastoma multiforme (GBM) cells display a highly invasive phenotype, a hallmark which counters effective surgical and radiotherapy strategies. Caveolin-1 (Cav-1) is the main structural and functional component of caveolae. The impact of the expression of Cav-1 within a range of tumour and tumour-associated stromal cells is variable with both oncogenic and tumour suppressive roles reported which appear to be both disease-specific and context-dependent. Our hypothesis is that Cav-1 serves as promoter of invasion of GBM cells. MATHERIALS AND METHODS: To investigate our hypothesis we used a lentiviral shRNA approach to silence Cav-1 in three GBM cell lines (U87, UP007, UP029) derived from adult brain tumours. We employed an in-vitro 3D cell-sprouting invasion assay with GBM cell spheres embedded in Matrigel. Quantification of invasion was undertaken using a novel image analysis tool or 3D systems, INSIDIA (ImageJ Macro for High-throughput Spheroid Invasion Analysis). Parallel migration and invasion studies were performed using a Boyden Chamber approach, as well as cell-cell adhesion assays. Activation of signalling pathways in 2D and 3D cultures were performed by proteomic array and Western Blot analysis. RESULTS AND CONCLUSION: GBM cells expressing Cav-1 (Cav-1 +ve) displayed a higher invasive capacity compared cells where Cav-1 had been silenced Cav-1 –ve), the latter also showing increased cell-cell adhesion. A significant finding from the signalling analysis was an inverse association between Cav-1 silencing and activation of AKT evidenced by increased phosphorylation at both Ser473 and Thr308 sites. Ongoing studies are exploring this signalling axis and its relationship to the invasive phenotype. CM and MG acknowledge Cancer Research Wales support. GP and HF acknowledge Brain Tumour Research support.